The Double-Edged Sword: Family Support, Stigma, and Family Care Dynamics among Families of Patients with Multidrug-Resistant Tuberculosis in Urban Areas of Bandar Lampung - Della Rachmadani; Dewi Ayu Hidayati; Bartoven Vivit Nurdin (UNIB Press, 2026)
Families play a crucial role in the recovery process of patients with multidrug-resistant tuberculosis (MDR-TB). Still, at the same time, they can be a source of stigma that exacerbates patients’ psychological and social conditions. This study aims to analyze family beliefs, forms of stigma within the family environment, and family behaviors toward MDR-TB patients in the urban area of Bandar Lampung. This study employs a qualitative, constructivist approach. Data analysis draws on Social Pathology Theory to understand stigma, prejudice, and discriminatory behavior as resulting from negative social constructions and misunderstandings about the disease. Data were collected through in-depth interviews, observations, and documentation involving seven key informants who were immediate family members of MDR-TB patients. Data collection reached saturation, at which point no new information was found. The results indicate that family stigma manifests in three main forms: feelings of shame, a tendency to blame the patient, and excessive fear of transmission. This stigma is reinforced by the misconception that MDR-TB is highly contagious, difficult to cure, caused by an unhealthy lifestyle, and a frightening disease. These family beliefs influence how patients are treated, ranging from avoidance and discrimination to support during treatment. These findings underscore the importance of family-based health education in correcting misconceptions and reducing stigma, thereby improving the quality of family support and treatment adherence among patients with MDR-TB.